2022
DOI: 10.1177/09708464221096903
|View full text |Cite
|
Sign up to set email alerts
|

Digital Analysis of the Transformation of Institutions in the Knowledge and Innovation System of the Handmade Carpet Industry

Abstract: The Indian handmade carpet industry has various economic, social and national dimensions. The rich diversity of Indian carpets is a symbol of different cultures and traditions in this country like India and Iran. To ensure the sustainability of the knowledge digital and innovation system of the handmade carpet industry, in addition to considering the dominant approaches of the innovation systems, attention should be paid to the transformative approach that pursues holistic transformation in the production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The statement is valid as the findings of the study are only indicating the mediating role of facilitating conditions rather than any other variable of the UTAUT model. Therefore, legitimate to declare the study is inconsistent with, Yadav et al [34] . The same author [35] and Yadav et al [36] , indicated per-formance expectancy and effort expectancy as the potent variables associated with the adoption of Fin-Tech.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The statement is valid as the findings of the study are only indicating the mediating role of facilitating conditions rather than any other variable of the UTAUT model. Therefore, legitimate to declare the study is inconsistent with, Yadav et al [34] . The same author [35] and Yadav et al [36] , indicated per-formance expectancy and effort expectancy as the potent variables associated with the adoption of Fin-Tech.…”
Section: Resultsmentioning
confidence: 97%
“…Cronbach's Alpha (α), Goldstein rho & composite reliability. However, according to Nunnally [21] , the values of Cronbach's Alpha and Composite Reliability must be greater than 0.7 and Goldstein rho is also termed as a better reliability evaluator than Cronbach's Alpha, Žukauskas [20] and Yadav et al [41] . Therefore, in association with these criteria table is suffi- ciently fulfilling the requirements of internal reliability (α), construct reliability, and composite reliability.…”
Section: Statistical Testing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…"Magia Raptzen (2011)," the handicraft expert, observed that academicians, researchers, and students can learn the value and potential of craft in terms of marketing economy and supply methods and utilize their knowledge, aptitude, and skills to increase the income of workers and artisan involved in the handicraft industries. The findings show that there is a large gap in the worth and quality of craft for the learners in both the control groups and experimental groups [43].…”
Section: Review Of Literaturementioning
confidence: 90%
“…So, it must make strategies for their development in the handicraft industry [27]. In the case of formal and informal knowledge transformation in the handmade carpet industry, Yadav et al analyzed the good criteria for the transformation of institutions [26]. To develop business strategies for upgrading the handicraft artisan's skills, there is a need for special strategies [31].…”
Section: Review Of Literaturementioning
confidence: 99%